Pengembangan Konten E-Learning BGTK Bali Berbasis ICARE Untuk Meningkatkan Kompetensi Kepribadian Guru - Kadek Dwi Wahyuni; Ni Nyoman Parwati; Ketut Agustini (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aims to develop e-learning content based on the ICARE model (Introduce, Connect, Apply, Reflect, Extend) on the Learning Management System (LMS) platform of Bali Province Center for Teachers and Education Personnel (BGTK). This development specifically addresses the need to improve teachers' personality competencies, given the current sub-standard competency levels and limited access to flexible, interactive training. Utilizing the Research and Development (R&D) method with the ADDIE model, this study involved 30 elementary school teachers in Denpasar as field trial subjects. Data collection instruments included expert validation sheets, the User Experience Questionnaire (UEQ), the System Usability Scale (SUS), and learning outcomes tests (pre-test and post-test). The results indicate that the e-learning media is highly valid, achieving a coefficient score of 1.00 from both media and content experts. The media also met the criteria for high practicality, falling into the "Excellent" category, and received highly positive user feedback. Comparative analysis showed a significant improvement in teachers' personality competence, with mean scores increasing from 66.8 to 86.2. Furthermore, effectiveness analysis placed the impact of this development in the "large effect" category. In conclusion, this e-learning content is effective in improving teacher personality competence in an independent and systematic manner.